2013
DOI: 10.1016/j.bpj.2013.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Motion near a Vessel Wall or Thrombus Surface in Two-Dimensional Whole Blood Simulations

Abstract: Computational simulations using a two-dimensional lattice-Boltzmann immersed boundary method were conducted to investigate the motion of platelets near a vessel wall and close to an intravascular thrombus. Physiological volume fractions of deformable red blood cells and rigid platelet-size elliptic particles were studied under arteriolar flow conditions. Tumbling of platelets in the red-blood-cell depleted zone near the vessel walls was strongly influenced by nearby red blood cells. The thickness of the red-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 31 publications
(40 reference statements)
2
61
0
Order By: Relevance
“…Modeling the thrombus as a porous structure predicts that the depletion layer narrows with increasing porosity (Skorczewski et al 2013), thus squeezing platelets into the thrombus (Figure 2 e ) and possibly increasing the likelihood of platelet aggregation. Even without interstitial fluid flow through a clot, the presence of a stenosis in a vessel (Figure 2 d ) may enhance platelet deposition (Wang et al 2013a).…”
Section: Platelet Margination In Flowing Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling the thrombus as a porous structure predicts that the depletion layer narrows with increasing porosity (Skorczewski et al 2013), thus squeezing platelets into the thrombus (Figure 2 e ) and possibly increasing the likelihood of platelet aggregation. Even without interstitial fluid flow through a clot, the presence of a stenosis in a vessel (Figure 2 d ) may enhance platelet deposition (Wang et al 2013a).…”
Section: Platelet Margination In Flowing Bloodmentioning
confidence: 99%
“…Platelet motions from three different near-wall starting locations are shown. Panel e modified with permission from Skorczewski et al (2013).…”
Section: Figurementioning
confidence: 99%
“…Several suppositions have emerged in an attempt to explain these observations. The mechanism of self-regulation of thrombosis has been ascribed to biochemical reactions and platelet activation (7,9), the changing porosity of the thrombus (10), or the nonuniform structure of the thrombus (6)(7)(8)(9)(10)(11)(12), but it is still a subject of debate. Early studies demonstrated that thrombosis is governed mainly by two competing factors: the rate of platelet attachment from the bloodstream and the intensity of hydrodynamic forces that prevent platelets from adhering to the thrombus (8,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…At normal haematocrit values platelets slide (rather than tumble) through the CFL, with more of their surface exposed to the vessel wall -possibly maximising their probability of adhesion. Using the method of Crowl and Fogelson, Skorczewski et al 77 studied the dynamics of platelets in the CFL at a thrombus site. They found that the CFL is narrowed at the thrombus site, leading to a closer contact between the thrombus and platelets; it is thought that this may enhance the likelihood of platelet adhesion and promote further thrombus growth.…”
Section: Plateletsmentioning
confidence: 99%